An Unusual Case of Lingual Alveolar Soft Part Sarcoma During Pregnancy - Omer L. Tapisiz; Tayfun Gungor; Emin Ustunyurt; Bulent Ozdal; Umit Bilge; Leyla Mollamahmutoglu (Elsevier, 2008)
Objective: We report a case of alveolar soft part sarcoma (ASPS) of the tongue that presented in the third trimester of pregnancy. Case Report: An 18-year-old, gravida 1, para 0, woman with ASPS of the tongue in the 31st week of pregnancy was described. Approximately 4 months after her first diagnosis, she was referred to our clinic for the delivery of her baby and additional treatment. At 32 weeks of gestation, a healthy male infant weighing 2,220 g was delivered by cesarean section. After an uneventful postoperative course, she was referred to the Department of otorhinolaryngology and maxillofacial surgery for further investigation and treatment. Conclusion: ASPS ofthe tongue presenting in pregnancy is an extremely rare combination, and to our knowledge, this is the first reported case in the English literature. The diagnostic and therapeutic management ofthe pregnant patient with cancer, like ASPS, is especially difficult, because it involves both the mother and fetus. [Taiwan J Obstet Gynecol 2008;47(2):21 2-21 4]